Siloxanes: Viable Alternatives for PFAS in Essential Applications? - Donahue-Boyle, EM; Nascimento, MA; Kah, M; Padhye, LP; Chen, JLY; Leitao, EM (The Royal Society of Chemistry, 2026)
Per- and polyfluoroalkyl substances (PFAS) are highly valued for their thermal and chemical stability, oil and water repellency, and fire-suppression capabilities. However, they are increasingly being regulated because of their environmental persistence and bioaccumulative potential, leading to a search for alternatives across a variety of material types. Siloxanes are an under-explored class of compounds that offer many similar properties to PFAS (particularly their hydrophobicity and thermal stability) and degrade readily in the environment. Siloxane-based PFAS alternatives are commercially available for non-essential applications, such as water-repellent coatings and cosmetics, but the applicability of siloxanes in many other critical applications is not as well understood. To date, no broad comparison between siloxanes and PFAS in critical applications has been made. This critical review presents potential candidates for viable, siloxane-based PFAS replacements across materials and surfactant science applications, including omniphobic coatings, firefighting foams, mould release coatings, high-performance surfactants, and processing aids for semiconductor manufacturing. Particular emphasis is placed on compounds that are oleophobic, have low surface tension, or demonstrate high chemical stability under harsh operating conditions. In each substitution case, we discuss the properties conferred by the PFAS, analyse the current ability of state-of-the art siloxanes to satisfy the application's performance requirements, and recommend directions for future research towards the design and assessment of high-value, environmentally benign siloxane surfactants.
Keywords: 34 Chemical Sciences; 3406 Physical Chemistry; Endocrine Disruptors